Diagnostic biologique de l’infection à Sars-CoV-2 : stratégies et interprétation des résultats - Hantz, Sébastien (Rev Francoph Lab, 2020)
In response to the emergence of Sars-CoV-2 responsible for a global pandemic, a large number of diagnostic tests have been developed and brought to market in a very short period of time. RT-PCR on nasopharyngeal swab samples is the reference method for the diagnosis and screening of Sars-CoV-2 infection, but the tests developed are highly variable in terms of sensitivity and turnaround time. Antigenic tests generally have lower sensitivity but have the advantage of simpler and faster implementation. In front of Covid-19 symptoms with negative RT-PCR results, serology can be recommended with IgM and IgG assays. Serology is also a relevant tool for epidemiological studies. However, it is important to remember that the level of anti-Sars-Cov-2 antibodies decreases over time and can therefore impact the results of sero-epidemiological studies. Despite the need to respond rapidly to an urgent diagnostic need, it remains essential to validate the methods chosen on a well-characterized panel of samples, as the performance of certain tests is sometimes unsatisfactory to ensure a reliable diagnosis.